1995
DOI: 10.2174/092986650202220524124754
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Wild-Type Growth Hormone at 2.5 a Resolution

Abstract: The three-dimensional structure of uncomplexed natural sequence recombinant human growth hormone has been determined to 2.5 A. resolution by means of X-ray crystallographic techniques. The structure was solved using molecular replacement with a model of a hGH variant. The crystallographic refinement of the structure gave a final R-factor of 21.3% for data in the range from 8 to 2.5 A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The SAXS curves were buffer subtracted and analyzed with the SAS Data analysis module from the ATSAS 2.5.0 package, and the deduced values are found in Table . A rigid body refinement using a HSA model in complex with octadecanoic acid and two growth hormone molecules was applied in the ATSAS SASREF module using 15 Å distance constraints from residue 101 of growth hormone to residues 209 (FA6) and 502 (FA5) of HSA. The SAXS data and models are deposited in the small-angle scattering biological data bank () with the accession codes listed in Table .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The SAXS curves were buffer subtracted and analyzed with the SAS Data analysis module from the ATSAS 2.5.0 package, and the deduced values are found in Table . A rigid body refinement using a HSA model in complex with octadecanoic acid and two growth hormone molecules was applied in the ATSAS SASREF module using 15 Å distance constraints from residue 101 of growth hormone to residues 209 (FA6) and 502 (FA5) of HSA. The SAXS data and models are deposited in the small-angle scattering biological data bank () with the accession codes listed in Table .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The percentage of secondary structure components for hGH in the bulk solution and the complex with polymers are listed in Table 2. The helical content of the reference crystal structure 38 is 54.3%. The results in Table 2 show that in the aqueous medium, the percentage of the protein α-helices (54.82%) is higher than the reference molecule, and it can be concluded that the water environment does not interfere with the hGH secondary conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The starting structure of the human growth hormone for the MD simulations was taken from the Protein Data Bank (PDB ID: 1HGU). 38 Missing residues and atoms in the crystal structure were added using MODELLER software. 39 The study is aimed at linear polymers and copolymers of 30 units in length.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the crystallographic structures of receptorbound and free human growth hormone reveals that GH is an anti-parallel four-helix bundle protein containing two disulfide bridges, Cys53 -Cys165 and Cys182 -189 [3,24]. The two structures are closely similar, except for some short helices connecting the four major helical segments.…”
Section: Gh Isoformsmentioning
confidence: 99%